PERAN KINESTESIS DALAM PEMBELAJARAN MOTORIK - Setyo Nugroho (Jurnal Cakrawala Pendidikan, 2005)
AbstractThis article describes the role of kinesthesis in motor learning. It starts with a definition that kinesthesis is generally regarded asa feeling or awareness of body position and body movement. But there are four factors seemingly quite common in definitions of kinesthesis: positioning of body segments, precision of movement, balance, and spatial orientation. Any appropriate reference explaining the reception and tramsmission of kinesthetic information during movement has not yet been determined to the satisfaction of all those working in this area. Traditionally, it has been assumed that the proprioceptor in the muscles represents the source of kinesthesis. The possibility of improving the capability of the kinesthetic organ of sense has been a subject of considerableinterest in discussions among instructors of physical education. But there is, as yet, no convincing evidence that kinesthesis can be improved. It is generally stated, though, that the more one practices in repeating a certain movement, the more skillful one becomes in making that movement. One can feel, however, that feeling and balance, as main elements of kinesthesis, can be improved through increased practice frequency and or creation of a conducive condition.Key words: kinesthesis, positioning of body segments, precision of movement, balance, and spatial orientation